2019
DOI: 10.1016/j.midw.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

‘It definitely made a difference’: A grounded theory study of yoga for pregnancy and women's self-efficacy for labour

Abstract: Objective: To explore women's experience of attending yoga for pregnancy classes in order to generate a theory about which aspects, if any, are effective in enhancing self-efficacy for labour and birth. Design: A longitudinal grounded theory study. Methods: Semi-structured interviews were undertaken with women before they started yoga for pregnancy classes, after they had attended at least six classes, and finally, postnatally. Interview transcripts were analysed using constructive grounded theory and a self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 72 publications
2
12
0
2
Order By: Relevance
“…The current study deals with a unique population of primigravid women in the ultra-orthodox religious Jewish community of Israel. The literature showed that fear of childbirth was associated with reduced maternal confidence [ 1 , 2 , 3 ], increasing anxiety, and reduced self-efficacy [ 5 , 8 ]. The aim of the present study was to examine the contribution of childbirth preparation courses to a woman’s ability to cope successfully with childbirth by raising her self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study deals with a unique population of primigravid women in the ultra-orthodox religious Jewish community of Israel. The literature showed that fear of childbirth was associated with reduced maternal confidence [ 1 , 2 , 3 ], increasing anxiety, and reduced self-efficacy [ 5 , 8 ]. The aim of the present study was to examine the contribution of childbirth preparation courses to a woman’s ability to cope successfully with childbirth by raising her self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of childbirth has been found to be directly related to fear of pain, lowering mother’s confidence in her natural ability to give birth and leading to the use of painkillers and instrumental births [ 1 ]. “Tocophobia” refers to anxiety about childbirth and seeking to give birth by caesarean section even though there is no medical reason for it [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on several studies, it is stated that yoga can help provide peace of mind and soul because it can be used as a stress coping (Pratignyo, 2014) and increasing self-efficacy (Campbell and Nolan, 2019).…”
Section: Rumah Bersalin Marga Mulya Mojosongomentioning
confidence: 99%
“…Kelas ibu hamil sangat berpotensi mengajarkan ibu dalam menyusun strategi saat bersalin serta membantu dalam menjawab kebingungan terkait kesehatannya. Kelas ibu hamil memiliki metode pendekatan yang terbukti efektif dalam meningkatkan pengetahuan ibu hamil [19] . "kita kan kelas ibu hamil tiap bulan" (IU.H, 1 Maret 2019).…”
Section: "Informasi Edukasi Oleh Bidan-bidan DI Desa" (Iun 2 Maret unclassified